Rhythmic, Melodic, and Phonetic Elements in Ghazal Poetry (Ustozlar uchun, 2025)
Abstract: This thesis explores the rhythmic, melodic, and phonetic dimensions of ghazal poetry, focusing on their combined role in shaping the aesthetic, emotional, and cultural resonance of the genre. As a form deeply rooted in Persian, Arabic, and Turkic literary traditions, the ghazal has long captivated readers and listeners through its musicality and linguistic elegance. By examining the interplay of rhythm, melody, and sound devices, this research highlights how ghazal poets such as Hafiz, Alisher Navoi, and Ghalib employed linguistic artistry to heighten emotional intensity, create lyrical beauty, and ensure oral memorability. The study argues that ghazal poetry cannot be fully understood without appreciating its acoustic elements, which serve as a bridge between written text and oral performance. Findings contribute to the broader study of poetics, linguistics, and comparative literature.